THE CONCEPT OF HUMAN DEVELOPMENT IN THE NOTION OF ECONOMIC MAN: SECULAR AND ISLAMIC PERSPECTIVE - Hafas Furqani (Sharia and Law Faculty, 2017)
Economics subject as study has shifted from the study of wealth (material resources) to the study of human behavior when Lionel Robbins published his monumental work in 1932. Economics as a discipline is interested to study the economic agent behavior in making decisions of allocation resources which are scarce relative to human wants which are unlimited. To some scholars, the subject matter of Islamic economics is similar, i.e., the behavior of economic agent. Both economics, definitely, have several doctrines and assumptions of the nature of economic agent behavior related to their economic life an also the notion of economic man development and progress. Mainstream economics conceives homo economicus as the economic agent who is rational, pursuing self- interest, maximizing his own utility, and consider values judgments as exogenous variables. Islamic economics, on the other hand, conceives homo Islamicus as the economic agent who is Islamically rational, pursuing multiple interests (self-interest together with God-interest, social-interest, and the environment-interest), and considers ethics as endogenous variables that would shape the behavior of Islamic man in economic analysis. The concept of human progress and development is outlined in accordance with this â€œcharacteristicsâ€ of economic man and his â€œgoalsâ€ to be achieved. This paper will explore the conceptual differences of economic man in Islamic and conventional framework as well as the concept of human development in both traditions.